2019
DOI: 10.24176/re.v9i2.3379
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Forum Diskusi Pada E-Learning Berbasis Moodle Untuk Meningkatkan Partisipasi Belajar

Abstract: The study aims to find out the effectiveness of the discussion forum on Moodle based elearning to improve students learning participation. The study employs pre-experiment method with one group pretest-posttest design and analysis method uses non-parametric statistics with T-test. The study is conducted at Information Technology Department of Faculty of Education at University of Technology Yogyakarta. The research sample is taken from the fourth semester student of Information Technology Education Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 3 publications
1
19
0
12
Order By: Relevance
“…This is in line with the results of this study which showed that 84% of students of the Physical Education Study Program had learning outcomes that were included in the very high category. The results of this study are in line with the results of research conducted by Fatmawati (2019) which found that discussion forums in learning conducted through Moodle-based e-learning were able to increase student learning participation when compared to discussions that occurred in conventional or classical classes face-to-face with an increase value of 37%. E-learning was effective in the midst of the covid-19 pandemic (Ali et all 2021;Saeed & Hammood, 2021;Shaik Alavudeen et al, 2021).…”
Section: Figure 5 Student Learning Outcomes In Online Learningsupporting
confidence: 89%
“…This is in line with the results of this study which showed that 84% of students of the Physical Education Study Program had learning outcomes that were included in the very high category. The results of this study are in line with the results of research conducted by Fatmawati (2019) which found that discussion forums in learning conducted through Moodle-based e-learning were able to increase student learning participation when compared to discussions that occurred in conventional or classical classes face-to-face with an increase value of 37%. E-learning was effective in the midst of the covid-19 pandemic (Ali et all 2021;Saeed & Hammood, 2021;Shaik Alavudeen et al, 2021).…”
Section: Figure 5 Student Learning Outcomes In Online Learningsupporting
confidence: 89%
“…A Moodle resource is a feature that a lecturer may apply to assist learning, similar to a link or a file. Moodle supports a comprehensive design of resource classification that lecturers may combine with the courses (Fatmawati, 2019;Zabolotniaia et al, 2020). In the edit form, the lecturers may attach different sources completed in the drop-down menu, and also appears as the link, which has a picture in front of it, describing the variety of resources.…”
Section: Discussionmentioning
confidence: 99%
“…Moodle also has complex possibilities and instruments available for application. The system supports communication between the instructor and students, and students can also interact with each other (Fatmawati, 2019;Nugroho & Iqbal Arrosyad, 2020).…”
Section: "I Change My Position To the Co-learning; The Situation Is To Prevent The Uncomfortable Moodle Class" (Respondent 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…Partisipasi tersebut diukur dari seberapa besar keterlibatan anggota dalam aktivitas-aktivitas kelompok. (Fatmawati, 2019). Pada penelitian ini partisipasi belajar dilakukan dengan tatap muka virtual.…”
Section: Hasil Dan Pembahasanunclassified